Decorin-mediated oncosuppression – a potential future adjuvant therapy for human epithelial cancers - Annele Orvokki Sainio; Hannu Tapio Järveläinen (British Pharmacological Society, 2022)
Currently, the multifaceted role of the extracellular matrix (ECM) in tumorigenesis has been realized. One ECM macromolecule exhibiting potent oncosuppressive actions in tumorigenesis is decorin, the prototype of the small leucine-rich proteoglycan gene family. The actions of decorin include its capability to function as an endogenous pan-receptor tyrosine kinase inhibitor, a regulator of both autophagy and mitophagy, as well as a modulator of the immune system. In this review, we will discuss these topics in more detail. We will also give a summary of preclinical studies exploring the value of decorin-mediated oncosuppression as a potential future adjuvant therapy for epithelial cancers.